2020
DOI: 10.1038/s41467-020-15995-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging-regulated anti-apoptotic long non-coding RNA Sarrah augments recovery from acute myocardial infarction

Abstract: Long non-coding RNAs (lncRNAs) contribute to cardiac (patho)physiology. Aging is the major risk factor for cardiovascular disease with cardiomyocyte apoptosis as one underlying cause. Here, we report the identification of the aging-regulated lncRNA Sarrah (ENSMUST00000140003) that is anti-apoptotic in cardiomyocytes. Importantly, loss of SARRAH (OXCT1-AS1) in human engineered heart tissue results in impaired contractile force development. SARRAH directly binds to the promoters of genes downregulated after SARR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 61 publications
3
53
0
3
Order By: Relevance
“…For context, oxidative stress and mitochondrial membrane potential are both hallmarks of ageing, 30 and loss of cells through apoptosis is also representative of ageing; such cell loss can be regulated by caloric restriction. 83 The effect of the deceleration of platelet ageing is consistent with better controlled activation of platelets with reduced P-selectin level (figure 4F). Functional analysis of hearts and vessels also shows that some of the cardiovascular function were improved and rejuvenated.…”
Section: Discussionsupporting
confidence: 67%
“…For context, oxidative stress and mitochondrial membrane potential are both hallmarks of ageing, 30 and loss of cells through apoptosis is also representative of ageing; such cell loss can be regulated by caloric restriction. 83 The effect of the deceleration of platelet ageing is consistent with better controlled activation of platelets with reduced P-selectin level (figure 4F). Functional analysis of hearts and vessels also shows that some of the cardiovascular function were improved and rejuvenated.…”
Section: Discussionsupporting
confidence: 67%
“…Inhibition of Sarrah induces caspase activity in mouse and human cardiomyocytes, promoting apoptosis. Gene set enrichment analysis after SARRAH silencing showed enrichment of apoptosis-related pathways, corroborating previous observations ( Trembinski et al, 2020 ). SARRAH was also found to directly bind to the promoters through RNA-DNA triplex helix structures, suggesting that its binding may activate gene expression.…”
Section: A Role For Lncrnas In Heart Regenerationsupporting
confidence: 90%
“…More recently, Trembinski et al (2020) identified lncRNA SCOT1-antisense RNA regulated during aging in the heart ( SARRAH ), whose expression declines during aging. Inhibition of Sarrah induces caspase activity in mouse and human cardiomyocytes, promoting apoptosis.…”
Section: A Role For Lncrnas In Heart Regenerationmentioning
confidence: 99%
See 2 more Smart Citations